2020
DOI: 10.5152/tjg.2019.19362
|View full text |Cite
|
Sign up to set email alerts
|

Attendance to a “normal delivery” of choledocholithiasis

Abstract: Stem cells for pancreatitis 425 Gastric injury and bacterial overgrowth 433 The effect of visceral fat on SMA configuration 451 Antiplatelet agents in ulcerative colitis 459 Differentiation of BMSCs into intestinal ce 466 GERDOFF ® efficacy in patients with GERD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Murabayashi et al [ 17 ] reported CBD stone in cholangitis spontaneously passed during computed tomography. Moreover, there have on live spontaneous migration of CBD stone during endoscopy [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murabayashi et al [ 17 ] reported CBD stone in cholangitis spontaneously passed during computed tomography. Moreover, there have on live spontaneous migration of CBD stone during endoscopy [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Murabayashi et al reported an 85-year-old man with cholangitis from one large CBD stone (15 mm) that had spontaneous passed during computed tomography [ 17 ]. Itoi et al [ 18 ] and Cerezo-Ruiz et al [ 19 ] showed single CBD stone can spontaneous passed during endoscopy in patient with cholangitis.…”
Section: Discussionmentioning
confidence: 99%